Prediction of cross-reactivity between human IgA and manatee (Trichechus manatus) IgA: A computational biology study (2024)
The Caribbean manatee (Trichechus manatus), as an aquatic mammal, has experienced a critical population decline due to various anthropogenic factors. Although conservation programs have been implemented to protect the current population and mitigate the damage caused, these have not focused on the study of the immune system of this animal, particularly the effects of the lack of breastfeeding in orphaned manatees in captivity. In order to conduct these studies, an immune component of great importance is immunoglobulin A (IgA), which is found in greater quantities in secretions such as milk. This Ig plays an important role in establishing protection in mucous membranes and a healthy microbiota due to its interactions with microorganisms. However, there are currently no specific reagents for this species. In this study, computational biology tools were applied to predict cross-reactivity between available anti-IgA reagents and manatee IgA by identifying species that share high homology at sequence, three-dimensional structure, and B-Cell epitope identity levels with manatee IgA. Human IgA was selected due to its high degree of homology, the quality of the sequence found and the quantity of available polyclonal anti-IgA conjugates. Based on the results obtained, there is a high possibility that polyclonal reagents for the detection of human IgA can cross-react with manatee IgA. This allows for future serological studies to identify IgA in manatee milk and thus enhance immune system research in these animals, including these data in conservation efforts.